A novel interdisciplinary approach for building archaeology: The integration of mortar "single grain" luminescence dating into archaeological research, the example of Saint Seurin Basilica, Bordeaux. (August 2018) - Urbanová, P.; Michel, A.; Cantin, N.; Guibert, P.; Lanos, P.; Dufresne, P.; Garnier, L.
Abstract: This paper deals with new strategies for dating the construction of ancient monuments, one of the most topical issues in archaeology. Our approach is demonstrated by the study of an emblematic early medieval Basilica Saint Seurin in Bordeaux whose oldest building phases have never been well-understood and dated before due to the lack of written sources and archaeological findings. We mainly focus on the analyses of mortar as an omnipresent and non-recyclable material whose making is undoubtedly contemporary to the building process. For the first time, we integrated a novel, recently validated protocol for dating historical mortar through optically stimulated luminescence using the « single grain technique » (SG-OSL) into archaeological research. The present work arises from close and continuous collaboration between archaeologists and archaeometers both in situ and during post-excavation analyses. SG-OSL dating of mortar, as the most innovative aspect of the study, was combined with mortar characterization, radiocarbon dating of charcoals and partly also with archaeomagnetic and thermoluminescence dating of bricks for a cross-check of chronological data. We identified and dated several independent building phases in the crypt of the present church where mortar was the only building material preserved. By combining physical dating methods with stratigraphic constraints based on archaeological interpretations, all the findings were used to construct a chronological model that proves continuity in occupation of the site between the 5th and the 12th centuries, reflecting its high cultural and symbolic value. By the inter-connection of mortar dating by SG-OSL with archaeology and other fields of archaeometry, we set up a renewed interdisciplinary working model for building archaeology that opens interesting perspectives for the future of this research field. Highlights: Novel strategy for establishing chronologies of early medieval monuments is presented. Archaeology was combined with "single grain" OSL mortar dating in an integrated work. Hiatus in the history of the site was clarified through interdisciplinary approach. Several building phases were distinguished thanks to "single grain" OSL mortar dating. Continuity in occupation of the site was proved through chronological modeling.